Factors associated with delaying medical care: cross-sectional study of Nebraska adults - Kendra L. Ratnapradipa; Snehal Jadhav; Josiane Kabayundo; Hongmei Wang; Lisa C. Smith (BMC, 2023)
Abstract Background Delayed medical care may result in adverse health outcomes and increased cost. Our purpose was to identify factors associated with delayed medical care in a primarily rural state. Methods Using a stratified random sample of 5,300 Nebraska households, we conducted a cross-sectional mailed survey with online response option (27 October 2020 to 8 March 2021) in English and Spanish. Multiple logistic regression models calculated adjusted odds ratios (aOR) and 95% confidence intervals. Results The overall response rate was 20.8% (n = 1,101). Approximately 37.8% of Nebraskans ever delayed healthcare (cost-related 29.7%, transportation-related 3.7%), with 22.7% delaying care in the past year (10.1% cost-related). Cost-related ever delay was associated with younger age [< 45 years aOR 6.17 (3.24-11.76); 45-64 years aOR 2.36 (1.29-4.32)], low- and middle-income [< $50,000 aOR 2.85 (1.32-6.11); $50,000-$74,999 aOR 3.06 (1.50-6.23)], and no health insurance [aOR 3.56 (1.21-10.49)]. Transportation delays were associated with being non-White [aOR 8.07 (1.54-42.20)], no bachelor's degree [≤ high school aOR 3.06 (1.02-9.18); some college aOR 4.16 (1.32-13.12)], and income < $50,000 [aOR 8.44 (2.18-32.63)]. Those who did not have a primary care provider were 80% less likely to have transportation delays [aOR 0.20 (0.05-0.80)]. Conclusions Delayed care affects more than one-third of Nebraskans, primarily due to financial concerns, and impacting low- and middle-income families. Transportation-related delays are associated with more indicators of low socio-economic status. Policies targeting minorities and those with low- and middle-income, such as Medicaid expansion, would contribute to addressing disparities resulting from delayed care.